Phytochemical profiling, antibacterial, antifungal and antioxidant evaluation of Acrotrema arnottianum Wight - An ethnomedicinal plant - Ashokan, Akhil; Sreeranjini, S. (Current Botany, 2025)
Acrotrema arnottianum Wight (Dilleniaceae) is a perennial herb that grows in damp, shaded areas. It is native to the Western Ghats of Kerala and Tamil Nadu, where it is used in traditional medicine by tribal people, including the Malavedans of Kerala, to treat baldness and hair loss. Histochemical localisation of stem, petiole and midrib was performed to determine the localisation of flavonoids, phenols, alkaloids and tannins. The results indicated the presence of flavonoids and phenols. GC-MS analysis of ethanol extract revealed the presence of metabolites such as Linoleic acid, ethyl oleate, campesterol, tetradecanoic acid, Hexadecanoic acid, 3,7,11,15-Tetramethyl-2-hexadecen-1-ol, squalene and α-Tocopherol. GC-MS analysis of ethyl acetate extract showed the presence of α-Tocopherol-β-D-Mannoside, 3,7,11,15-Tetramethyl-2-hexadecen-1-ol, squalene, diphenols, phytol, eugenol and β-sitosterols. The antibacterial study against Staphylococcus aureus showed that ethyl acetate extract is more potent in inhibiting the growth (17±0.18) while the antifungal study against Candida albicans showed that ethyl acetate has a significant effect in inhibiting the growth (16±0.23), in dosage dependent manner. The antioxidant study revealed that ethanol extract has a higher IC50 value of 36.02±0.27. This study indicates that Acrotrema arnottianum is a source of pharmaceutically active secondary metabolite compounds.